Proceedings of the first workshop on Peripheral Machine Interfaces: going beyond traditional surface electromyography - Castellini, Claudio; Artemiadis, Panagiotis; Wininger, Michael; Ajoudani, Arash; Alimusaj, Merkur; Bicchi, Antonio; Caputo, Barbara; Craelius, William; Dosen, Strahinja; Englehart, Kevin; Farina, Dario; Gijsberts, Arjan; et al. (Frontiers in Neurorobotics, 2014)
One of the hottest topics in rehabilitation robotics is that of proper control of prosthetic devices. Despite decades of research, the state of the art is dramatically behind the expectations. To shed light on this issue, in June, 2013 the first international workshop on Present and future of non-invasive PNS-Machine Interfaces was convened, hosted by the International Conference on Rehabilitation Robotics. The keyword PNS-Machine Interface (PMI) has been selected to denote human-machine interfaces targeted at the limb-deficient, mainly upper-limb amputees, dealing with signals gathered from the peripheral nervous system (PNS) in a non-invasive way, that is, from the surface of the residuum. The workshop was intended to provide an overview of the state of the art and future perspectives of such interfaces; this paper represents is a collection of opinions expressed by each and every researcher/group involved in it.